2022
DOI: 10.1371/journal.pntd.0010544
|View full text |Cite
|
Sign up to set email alerts
|

Impaired in vitro Interferon-γ production in patients with visceral leishmaniasis is improved by inhibition of PD1/PDL-1 ligation

Abstract: Visceral leishmaniasis (VL) is a neglected tropical disease that causes substantial morbidity and mortality and is a growing health problem in Ethiopia, where this study took place. Most individuals infected with Leishmania donovani parasites will stay asymptomatic, but some develop VL that, if left untreated, is almost always fatal. This stage of the disease is associated with a profound immunosuppression, characterised by impaired production of Interferonγ (IFNγ), a cytokine that plays a key role in the cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…We have recently shown that PD-L1 was increased on all three subsets of monocytes at ToD [23]. Here we extended these results to EoT and show that PD-L1 was significantly decreased on classical and intermediate monocytes.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We have recently shown that PD-L1 was increased on all three subsets of monocytes at ToD [23]. Here we extended these results to EoT and show that PD-L1 was significantly decreased on classical and intermediate monocytes.…”
Section: Discussionsupporting
confidence: 74%
“…Singh et al showed that monocytes isolated from VL patients exhibit an anti-inflammatory phenotype, characterised by decreased parasite phagocytosis and impaired oxidative burst [22]. We have recently shown that PD-L1 is increased on all three subsets of monocytes at the time of VL diagnosis [23]. In the current study, we extend these results to the analyses of other molecules also involved in the modulation of T cell responses, such as CD40, CD80 and CD86.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…CD8 + T cells also provide a protective response through IFN-g production, which amplifies the early differentiation of CD4 + Th1 cells via IL-12 signaling and induces macrophage activation (6). One important mechanism underlying impaired T-cell immunity during either active or chronic human leishmaniasis is the substantial loss of effector functions in a process termed exhaustion (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%